EVALUASI RANAH KONGNITIF PADA SOAL SUMATIF AKHIR SEMESTER (SAS) DI SMK ISLAM AL MADINA PAGUYANGAN - Noviyanti, Intan; Septiani, Suci; Ameliya, Fitri Nur; Rizal, Ghulam Arif (Universitas Peradaban, 2024)
This study aims to describe the quality of the End of Semester Summative Questions (SAS) for the odd semester of the 2022/2023 school year based on data from the Indonesian Language subject class X TJA (Access Network Engineering) at SMK Islam Al Madina Paguyangan. Other improvements can also be made to the assessment standards, by gradually adapting them through learning models. Assessment of learning outcomes is expected to help students to further improve their ability to think at a higher level of Higher Order Thinking Skills (HOTS). Because through higher order thinking can encourage students to be able to think broadly and more deeply about the subject matter. The research method used is descriptive qualitative method. The purpose of this study is to describe the quality of the End of Semester Summative Questions (SAS) odd semester of the 2022/2023 school year based on data from the Indonesian language subject class X TJA (Access Network Engineering) at SMK Islam Al Madina Paguyangan. The results showed that there was an effect of students' initial ability on the completion of high order thinking questions in all aspects. Students are categorized as able to solve high order thinking questions. Keywords: kongnitif, HOTS, questions